Storia d'Italia di Francesco Guicciardini - Guicciardini, Francesco (Collezione de migliori autori italiani antichi e moderni, 1837)
In 1537 Francesco Guicciardini, adviser and confidant to three popes, governor of several central Italian states, ambassador, administrator, military captain — and persona non grata with the ruling Medici after the siege of Florence — retired to his villa to write a history of his times. His Storia d’Italia became the classic history of Italy — both a brilliant portrayal of the Renaissance and a penetrating vision into the tragedy and comedy of human history in general. Sidney Alexander’s readable translation and abridgment of Guicciardini’s four-volume work earned the prestigious 1970 P.E.N. Club translation award. His perceptive introduction and notes add much to the understanding of Guicciardini’s masterpiece.
Keywords: 10.Cover Damage; 1492-1559; 2.Damage; 22.stamp; Condition: Poor; History; Italie Histoire 1492-1559; Italy; Italy History 1492-1559; Paperback